2009
DOI: 10.1080/09511920802209058
|View full text |Cite
|
Sign up to set email alerts
|

Integration of product quality and tool degradation for reliability modelling and analysis of multi-station manufacturing systems

Abstract: The degradation of a tool component at an upstream station may cause the deterioration of the dimensional quality of a downstream workpiece. Meanwhile, the tool failure and its induced system reliability are affected by the incoming product quality from an upstream station. Quality and reliability interaction is thus introduced to address this interdependence in the reliability modeling and analysis of a multi-station manufacturing system. Moreover, an innovative quality and reliability integrated model is dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Chen and Jin (Yong and Jin, 2005) proposed a QR chain (Quality-Reliability Chain) to describe a process of multi-station transfer of component reliability and workpiece quality along the production process. Sun (Sun et al, 2009) proposed an integrated model of quality and reliability for multi-station manufacturing systems. The model usually sets the strength of interaction relationship between quality and reliability as a certain interaction coefficient to evaluate the reliability under this coefficient.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen and Jin (Yong and Jin, 2005) proposed a QR chain (Quality-Reliability Chain) to describe a process of multi-station transfer of component reliability and workpiece quality along the production process. Sun (Sun et al, 2009) proposed an integrated model of quality and reliability for multi-station manufacturing systems. The model usually sets the strength of interaction relationship between quality and reliability as a certain interaction coefficient to evaluate the reliability under this coefficient.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Multiple stages machining process is one of the important manufacturing processes in modern manufacturing field. Some researchers have done considerable amount of work on the product quality and machining system reliability [9][10][11] but the task reliability of the machining process, normally how to keep the quality of the machined products stable and how to establish the mathematical model to describe machining process reliability is not sufficient. So, this seems to be a prospective area to conduct research.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Jin 7 analyzed the co-effect of product quality and component reliability, and proposed a method for manufacturing system reliability analysis. Subsequently, Sun et al 8 revealed the dynamic evolution of this quality–reliability interaction in multi-station manufacturing systems. He et al 9 further extended the reliability of manufacturing systems by regarding the quality of produced products as an indicator of the reliability of manufacturing systems.…”
Section: Introductionmentioning
confidence: 99%